Strengthening Entrepreneurial Competencies Based on Creative Economy and Civic Education Values among High School Students - Monalisa Marta Siahaan; Rince Marpaung; Adelia Sitompul; Martogu Sinambela (Jurnal Pengabdian Masyarakat Bangsa, 2026)
The low level of entrepreneurial competence and the weak understanding of integrity among high school students indicate an urgent need to develop a learning model that integrates creative economy skills with the values of Civic Education (PPKN). This community service program aims to improve students’ entrepreneurial knowledge, skills, and character through creative economy training combined with the reinforcement of ethical and integrity-based values. The method used includes initial observation, needs assessment, workshop-based training, practical mentoring, the application of digital marketing, and evaluation through pre-tests and post-tests. The results show a significant increase in students’ understanding of entrepreneurial concepts, their ability to produce creative products, their digital marketing skills, and their application of integrity values in business practices. In addition, students succeeded in producing marketable products and demonstrated behavioral changes in honesty, responsibility, and teamwork. Overall, the program proved effective in improving students’ entrepreneurial competencies while strengthening character based on PPKN values, making it a potential sustainable learning model for schools.